The effect of glycerol with different purity on fattening performance in lambs - Behiç Coşkun; Esat Sami Polat; Emel Gürbüz; Fatma İnal (Eurasian Journal of Veterinary Sciences)
Aim: The effects of glycerol which is supplied from different production methods resulting in different purity were investigated on fattening lambs on nutrition performance. Materials and Methods: In the experiment, 32 of weaned Akkaraman Kangal male lambs, five months of age, were used in 4 groups, 8 animals each, formed as control, pure glycerol, and two various methanol acquired crude glycerol (4.14 and 9.80% methanol) groups. Experiment was continued 11 weeks including 1 week adaptation and 10 weeks experimental. Results: No significant difference was observed in terms of live weight (p>0.05). When daily live weight gains were compared, only in 56-70 days the crude glycerol group showed significance (p<0.05). There were no differences between groups in total feed consumption, but concentrate and roughage utilization rate were found better in 56-70 day, in the crude glycerol groups (p<0.05). Conclusion: It could be suggested that supplementation of lamb diets with up to 2.5% of glycerol when it was economic. Also, further evaluations are needed to determine the effect of higher levels of glycerol.